Testing two models describing how methylome-wide studies in blood are informative for psychiatric conditions. (August 2013) - Aberg, Karolina A; Xie, Lin Y; McClay, Joseph L; Nerella, Srilaxmi; Vunck, Sarah; Snider, Sarah; Beardsley, Patrick M; van den Oord, Edwin JCG
Aim: As the primary relevant tissue (brain) for psychiatric disorders is commonly not available, we aimed to investigate whether blood can be used as a proxy in methylation studies on the basis of two models. In the 'signature' model methylation–disease associations occur because a disease-causing factor affected methylation in the blood. In the 'mirror-site' model the methylation status in the blood is correlated with the corresponding disease-causing site in the brain.Materials, methods & results: Methyl-binding domain enrichment and next-generation sequencing of the blood, cortex and hippocampus from four haloperidol-treated and ten untreated C57BL/6 mice revealed high levels of correlation in methylation across tissues. Despite the treatment inducing a large number of methylation changes, this correlation remains high.Conclusion: Our results show that, consistent with the signature model, factors that affect brain processes (i.e., haloperidol) leave biomarker signatures in the blood and, consistent with the mirror-site model, the methylation status of many sites in the blood mirror those in the brain.